Optimizing the Potential Resources of Tahfidz Al Qur'an Educational Institutions: Quality Management Review - Noor, Hasni (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aimed to determine the management of improving the quality of resources at the Tahfidz Al-Qur'an Al Haromain Banjarmasin Institute. This research is descriptive qualitative research, using interviews, observations, and documentation as data collection techniques. The data analysis is carried out in stages: data reduction, data display and concluding. The study results indicate that the Tahfidz Al-Qur'an Al Haromain Educational Institution has managed to improve the management of the quality of resources in its institution. Planning efforts for all resources are carried out; the supervisory process is also carried out on the management of human resources, leaders, teachers, students, and parents, then the management of financial resources for those who apply mandatory infaq and for those who have donors have the control of donations from outside donors, management facilities and infrastructure and others that are by the existing theory.